Epidemiological characteristics of respiratory tract infections during and after the pandemic of COVID-19 from 2021 - 2023 in Shenzhen, southern China - Qiaoruo Jin; Sheng Yu; Jiuxin Qu (BMC Public Health)
Abstract Objective It is now understood that the COVID-19 pandemic and its associated containment measures have affected the epidemiology of other respiratory viruses. This study aimed to investigate respiratory pathogen infections in Shenzhen during and after the COVID-19 pandemic. Methods A retrospective analysis was conducted on test data from 24,814 patients at Shenzhen Third People’s Hospital between January 2021 and December 2023. The analysis focused on changes in detection rates, epidemiological characteristics, and clinical features of respiratory pathogens, including three viruses and eight bacteria. Results The overall positivity rate for respiratory viruses increased after the COVID-19 epidemic (P < 0.05), whereas no significant difference was detected in the overall positivity rate of most respiratory bacteria. Notably, the detection rates of influenza A and B increased after the COVID-19 epidemic, with influenza A showing the most significant increase from 4.5 to 10.8% (P < 0.05). Conversely, the detection rates of PAE and MRSA decreased significantly (P < 0.05), whereas those of HIN and SMA increased significantly (P < 0.05). The seasonal patterns of influenza A changed markedly, with a shift in peak occurrence and extended periods of high positivity. The age distribution of infections also shifted, with adults showing higher detection rates after the pandemic than school-aged children and elderly individuals did. Conclusion The removal of non-pharmaceutical interventions following the COVID-19 pandemic has significantly affected the epidemiological and seasonal patterns of certain respiratory pathogens in Shenzhen. These findings highlight the need for continuous surveillance of multiple respiratory pathogens and adaptive public health strategies in the post-pandemic era.